PENGGUNAAN VIRTUAL REALITY PADA GAME CREED: RISE TO GLORY-CHAMPIONS EDITION - Tasya Chayrina, Awalia Rahmatia, Adek Kurniawan, Nabila Aprilioni, Vidya Nofriza, Chelsy Putri, Rini (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
The use of Virtual Reality (VR) in the gaming industry has experienced rapid growth, providing immersive and immersive gaming experiences. This research explores the application of VR in the game "Creed: Rise to Glory - Champions Edition," a boxing game that utilizes VR technology to create a realistic experience. The research focus includes evaluating the gaming experience, health benefits, technical challenges, and social impacts of VR use. Findings show that the game provides a highly immersive experience with responsive motion controls, increasing players' emotional and physical engagement. Apart from being entertainment, "Creed: Rise to Glory - Champions Edition" also proves the potential to improve cardiovascular fitness, muscle strength and body coordination through physical activities integrated in the gameplay. However, VR use also faces challenges such as cybersickness and technical issues related to hardware performance. Social implications including potential social isolation due to excessive use are also a concern.Thus, this research concludes that VR has great potential to change the interaction paradigm in the gaming industry, but requires careful technical development and risk management to maximize its benefits for users.